The Atomic Layer Deposition Technique for the Fabrication of Memristive Devices: Impact of the Precursor on Pre-deposited Stack Materials - Quinteros, Cynthia Paula; Hardtdegen, Alex; Barella, Mariano; Golmar, Federico; Palumbo, Félix Roberto Mario; Curiale, Carlos Javier; Hoffmann Eifert, Susanne; Levy, Pablo Eduardo (IntechOpen, 2018)
Fil: Quinteros, Cynthia Paula. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina